Nanometer phase change particle dispersion strengthening tungsten alloy and preparation method thereof
By introducing HfO2@WO3 nanoparticles into the tungsten alloy and generating in situ by phase change, the problems of tungsten alloy's strength reduction and deformation failure in high-temperature environment are solved, and the excellent low-temperature toughness and high-temperature tensile strength of tungsten alloy are achieved.
Patent Information
- Application Number
- CN202411597049.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The strength of existing tungsten alloys is reduced in high temperature environment, making it difficult to meet the high-temperature service environment requirements of fusion reactors, and at the same time, it is prone to destructive failure during the deformation process.
By introducing HfO2@WO3 nanoparticles with core-shell structure into the tungsten matrix, nanoparticles are generated in situ by using the phase change during the rise and fall process to form a stable particle distribution, thereby enhancing the strain hardening ability of the tungsten alloy.
It realizes excellent strength and tensile strength of tungsten alloy at room temperature and high temperature, has good plasticity and strain hardening capabilities, and meets the needs of high-temperature environments such as fusion reactors.
Smart Images

Figure CN119433317A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fusion reactor plasma-facing wall materials, and in particular relates to a nano phase-change particle dispersion-strengthened tungsten alloy and a preparation method thereof. Background Art
[0002] The service temperature of tungsten materials is usually higher than 500℃. This sharp drop in high temperature strength is extremely unfavorable for tungsten materials that need to serve in the high temperature environment of nuclear fusion reactors. Therefore, it is necessary to continuously improve the low temperature toughness of tungsten materials while maintaining their strength at high temperatures, so that while improving processing performance, it can also better meet the high temperature service environment of future fusion reactors.
[0003] In order to improve the strength and toughness of metallic tungsten, people have carried out a lot of research and attempts, which have significantly improved the performance of tungsten. Adding high-melting-point second-phase carbide particles, such as zirconium carbide and hafnium carbide, to tungsten can play a role in dispersion strengthening and refining tungsten grains. However, during the high-temperature preparation process, the above-mentioned carbide particles are often easy to react with the oxygen in the tungsten matrix to form coarse oxide particles. These oxides are unstable in themselves and are prone to structural phase changes during the heating and cooling process: they are monoclinic structures at room temperature, transform into tetragonal structures at -1200°C, and transform into cubic structures at -2300°C. Structural phase changes will cause the oxide particles to expand (or shrink) by 4-6% in volume. The absolute volume change caused by large-sized particles is large, causing the particles to separate from the interface of the tungsten matrix and lose the strengthening effect. In order to suppress this phase change process, the applicant team disclosed a technical solution in the patent document "A high entropy ceramic nano twin particle dispersion reinforced tungsten alloy and its preparation method" with publication number CN115058628A: through the method of powder metallurgy, the oxygen impurities in the raw tungsten powder and the preparation process are controlled, and an appropriate amount of ZrC nanoparticles are introduced, and ZrC is used to react with the impurity oxygen in the tungsten matrix to generate Zr(W)-OC high entropy ceramic nano twin particles in situ. These high entropy ceramic nano twin particles are extremely stable, which suppresses the phase change process of the particles, thereby achieving a good strengthening effect. However, the particles prepared by the above technical solution only have a certain strengthening effect by pinning the grain boundaries and dislocations, and the improvement of the material deformation ability is small. Specifically, as a hard phase, the particles are prone to accumulate dislocations during the deformation process, resulting in stress concentration, and lack a certain way to relieve stress. It is manifested that it does not show any strain hardening ability during the tensile deformation process, and when the stress exceeds the yield strength, destructive failure will occur. In addition, the high temperature strength of the tungsten alloy prepared by the above technical solution is also insufficient. Figure 1 As shown, its strength at 800°C is only 815MPa, which is more than 50% lower than that at room temperature, making it difficult to meet the requirements for stable and safe operation of fusion reactors in high-temperature environments.
[0004] Therefore, in order to develop plasma-oriented tungsten alloys that meet the needs of future fusion reactors, it is necessary to further solve the problem of weak metallurgical bonding between coarse particles and the matrix in dispersion-strengthened tungsten alloys, and at the same time solve the problem of stress concentration caused by particle pinning dislocations, thereby improving the strain hardening ability of tungsten alloys and ultimately obtaining tungsten alloys with both excellent low-temperature toughness and high-temperature strength. Summary of the invention
[0005] The purpose of the present invention is to provide a nano phase change particle dispersion strengthened tungsten alloy and a preparation method thereof, further solve the problem of phase structure instability in the dispersion strengthened tungsten alloy, and improve the strain hardening ability of the tungsten alloy.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0007] The present invention provides a nano phase change particle dispersion strengthened tungsten alloy, the tungsten alloy is composed of a W matrix and HfO2@WO3 nanoparticles with a core-shell structure, wherein, by weight percentage, the content of the HfO2@WO3 nanoparticles with a core-shell structure is 0.2-2.0%, and the content of the W matrix is 97.5-99.8%. The particle size of the HfO2@WO3 nanoparticles is 5-150nm.
[0008] As a further optimization scheme of the above invention, the content of the HfO2@WO3 nanoparticles is 0.2-1.0% by weight, the content of the W matrix is 99.0-99.8% by weight, and the particle size of the HfO2@WO3 nanoparticles is 5-80 nm.
[0009] As a further optimization scheme of the above invention, the content of the HfO2@WO3 nanoparticles is 1.0-2.0% by weight, the content of the W matrix is 98.0-99.0% by weight, and the particle size of the HfO2@WO3 nanoparticles is 5-120 nm.
[0010] As a further optimization scheme of the above invention, the tungsten alloy is obtained by introducing nano HfH2 particles into a W matrix under a heated, pressurized and oxygen-free environment and performing thermomechanical deformation processing to utilize the phase change during the heating and cooling process to in-situ generate HfO2@WO3 particles with a core-shell structure on the W matrix.
[0011] The present invention also provides a method for preparing nano phase change particle dispersion strengthened tungsten alloy, comprising the following steps:
[0012] (1) Using tungsten powder (W) and nano-scale HfH2 powder as raw materials, mixing them evenly in an oxygen-free environment to obtain alloy powder;
[0013] (2) sintering the alloy powder under heating and pressure conditions to obtain a tungsten alloy block;
[0014] (3) Performing thermomechanical deformation processing on the tungsten alloy block to obtain the nano phase change particle dispersion strengthened tungsten alloy.
[0015] As a further optimization scheme of the above invention, the particle size of the tungsten powder is 0.2-6 μm, and the oxygen content is 800-2500 ppm. The particle size of the nano-scale HfH2 powder is 20-50 nm, and the oxygen content is ≤0.5 wt%.
[0016] As a further optimization solution of the above invention, the oxygen-free environment is one of argon, nitrogen or vacuum environment.
[0017] As a further optimization scheme of the above invention, the temperature of heating and pressurizing is 1600-1800°C, the pressure is 30-60MPa, and the sintering time is 0.2-4h.
[0018] As a further optimization solution of the above invention, the temperature of the thermomechanical deformation processing is 1000-1500°C.
[0019] As a further optimization scheme of the above invention, the thermomechanical deformation processing is one or a combination of two or more of high-energy forging, rolling, rotary forging and extrusion.
[0020] As a further optimization scheme of the above invention, the number of passes of the thermomechanical deformation processing is 4-10, the deformation amount of each pass is 5-20%, and the total deformation amount is ≥60%.
[0021] The beneficial effects of the present invention are:
[0022] 1) The present invention utilizes the phase change process of particles during the heating and cooling process to generate nano-sized HfO2@WO3 particles with a core-shell structure in situ. On the one hand, the core-shell structure ensures the stability of the particles and prevents them from coarsening and growing; on the other hand, the phase change of the particles enables the tungsten material to have a certain strain hardening ability. The tungsten alloy of the present invention has both excellent low-temperature toughness and high-temperature tensile strength, and exhibits plasticity at room temperature. The high-temperature tensile strength is much higher than the pure tungsten and conventional dispersion-strengthened tungsten alloys reported so far. The room temperature tensile strength is 1.30-1.60GPa, and the elongation is >7.5%; the tensile strength at 800°C is still maintained at 1.00-1.20GPa, which is much higher than other advanced tungsten materials reported in the literature. The preparation method of the tungsten alloy of the present invention is simple, scientific, efficient, and can be mass-produced. It is expected to be used in nuclear fusion reactor plasma-facing wall materials, national defense and industrial high-temperature components, etc.
[0023] 2) The present invention also provides a method for preparing nano phase change particle dispersion strengthened tungsten alloy. First, tiny nano HfH2 particles are introduced into the tungsten matrix, and the particles are used to react with the impurity oxygen in the tungsten matrix to generate monoclinic HfO2 particles in situ; the particles undergo phase change during the subsequent high-temperature mechanical deformation process, causing the volume of the particles to change, forming a large number of oxygen vacancies around the particles, and finally generating HfO2@WO3 particles with a core-shell structure. The above-mentioned HfO2@WO3 particles have two characteristics: First, the core-shell structure maintains the stability of the particles and prevents them from coarsening and growing. Second, the particles can undergo phase change under high temperature and stress, which improves the strain hardening ability of the material. Therefore, the nano HfO2@WO3 particle dispersion strengthened tungsten alloy has both excellent low-temperature toughness and high-temperature strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is the tensile curve of tungsten alloy at 800°C in the prior art;
[0025] Figure 2 This is a transmission electron microscope (TEM) image of the nano phase change particle dispersion strengthened tungsten alloy of the present invention;
[0026] Figure 3 The tensile stress-strain curve of the nano phase change particle dispersion strengthened tungsten alloy at room temperature and 800° C. according to Example 1 of the present invention;
[0027] Figure 4 It is a comparison chart of the tensile properties of the nano phase change particle dispersion strengthened tungsten alloy in the present invention and other tungsten materials in the prior art at 800°C. DETAILED DESCRIPTION
[0028] The present application is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technical personnel in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0029] Unless otherwise specified, the methods used in the present invention are all conventional methods known to those skilled in the art. The reagents and other materials used, unless otherwise specified, are all commercially available products. The instruments used, unless otherwise specified, are all conventional instruments known to those skilled in the art.
[0030] The particle size of tungsten powder (W) is 0.2-6 μm, and the oxygen content is 800-2500 ppm; the particle size of HfH2 powder is 20-50 nm, and the oxygen content is ≤0.5 wt%.
[0031] Example 1
[0032] The nano phase change particle dispersion strengthened tungsten alloy in this embodiment has the following specific steps for preparation:
[0033] (1) weighing tungsten powder and HfH2 powder in a weight percentage ratio of 99.8%:0.2%, and then placing them in a high-energy ball mill and uniformly mixing them in an argon protective atmosphere to obtain a mixed alloy powder;
[0034] (2) using a hot press furnace to densify and sinter the alloy powder of (1) under a vacuum environment, the sintering temperature is 1700° C., the pressure is 30 MPa, and the sintering time is 2 hours to obtain an alloy block with a high density;
[0035] (3) The tungsten alloy block obtained by densification sintering is subjected to 4 passes of high-energy forging at 1300±100°C, with a forging start temperature of 1400°C, a final forging temperature of 1200°C, and a total forging deformation of -75%. The density of the final forged sample is higher than 99%, and the target product is dense and crack-free.
[0036] The nano-phase change particle dispersion strengthened tungsten alloy prepared in this embodiment was analyzed by transmission electron microscope. Figure 2 As shown, the phase change particles are uniformly dispersed in the tungsten matrix, and most of them are less than 50nm in size. The energy spectrum analysis results of the particles show that the HfO2 particles are coated by the surface layer WO3 to form a core-shell structure.
[0037] In addition, the mechanical properties of the nano phase change particle dispersion strengthened tungsten alloy prepared in this embodiment were tested at different temperatures, and the results are as follows:
[0038] Tensile test: The strain rate during the test is constant at 2×10 -4 s -1 ,like Figure 3 As shown in a, the tensile strength of the target product nano phase change particle dispersion strengthened tungsten alloy at room temperature reaches 1.40GPa, and the elongation is >7.5%, indicating that the prepared tungsten alloy has good room temperature plasticity and low temperature toughness exceeds most of the bulk tungsten materials reported so far. The mechanical properties at 800℃ are shown in Figure 3 As shown in Fig. 2b, it can be seen that the prepared tungsten alloy shows a certain strain hardening ability after the yield point. Based on the small and stable particles and the characteristics of phase transformation at high temperature, the strength of the tungsten alloy prepared in this embodiment is still maintained at 1.08GPa at 800℃, while the tensile strength of various advanced tungsten materials reported at 800℃ is generally lower than 600MPa (such as Figure 4 The results show that the prepared tungsten alloy has excellent high temperature strength.
[0039] Example 2
[0040] The nano phase change particle dispersion strengthened tungsten alloy in this embodiment has the following specific steps for preparation:
[0041] (1) Weighing tungsten powder and HfH2 powder in a ratio of 99.0% by weight to 1.0% by weight, placing them in a high-energy ball mill, and uniformly mixing them under a vacuum environment to obtain a mixed alloy powder;
[0042] (2) using a plasma discharge sintering furnace to densify and sinter the alloy powder of (1) in an argon protection environment, the sintering temperature is 1600° C., the pressure is 40 MPa, and the sintering time is 0.2 hours to obtain an alloy block with a high density;
[0043] (3) The tungsten alloy block obtained by densification sintering in (2) is subjected to six passes of rotary forging at a temperature within the range of 1300±200°C, with a rotary forging start temperature of 1450±50°C and a final forging temperature of 1150±50°C. The deformation amount of each pass is 10-15%, and the total rotary forging deformation amount is -80%. The density of the final forged sample is higher than 99%, and the target product is dense and crack-free.
[0044] The phase change particles in the nano-phase change particle dispersion strengthened tungsten alloy prepared in this embodiment are less than 100nm in size, and more than 90% of the particles are inside the tungsten grains. The particles are composed of a WO3 shell layer on the surface and a HfO2 core layer inside. The strain rate in the uniaxial tensile test is a constant 2×10 -4 s -1 The performance test results show that the tensile strength of nano-phase change particle dispersion strengthened tungsten alloy at room temperature is as high as 1.30GPa, and the elongation is >7%, indicating that the material has plasticity at room temperature. Figure 4 As shown, the tungsten alloy prepared at 800°C has a certain strain hardening ability, and the tensile strength is maintained at 1.02 GPa.
[0045] Example 3
[0046] The nano phase change particle dispersion strengthened tungsten alloy in this embodiment has the following specific steps for preparation:
[0047] (1) Weighing tungsten powder and HfH2 powder in a weight percentage ratio of 98.0%:2.0%, then placing them in a high-energy ball mill and uniformly mixing them under a nitrogen protective atmosphere to obtain a mixed alloy powder;
[0048] (2) The alloy powder obtained in (1) is first pressed into a shape under a pressure of 150 MPa, and then the green body is placed in a hot isostatic press and pressurelessly sintered at 1700° C. for 6 hours under the protection of an inert gas, nitrogen, to obtain a relatively dense tungsten alloy block;
[0049] (3) The tungsten alloy block obtained by densification sintering in (2) is subjected to 6 hot rolling at 1400±100°C, with the starting temperature of rolling being 1450±50°C and the ending temperature being 1350±50°C. The deformation amount of each rolling is about 10%, and the total deformation amount of rotary forging is -60%. A tungsten alloy block with higher density is obtained;
[0050] (4) The tungsten alloy block after hot rolling in (3) is subjected to 4 passes of high-energy rate forging at 1200±100°C, wherein the initial forging temperature is 1300°C and the final forging temperature is 1000°C, until the total pressing amount reaches 65%, and the density of the final forged sample is higher than 99%, and the target product is dense and crack-free.
[0051] The phase change particles in the nano-phase change particle dispersion strengthened tungsten alloy prepared in this embodiment have a size of less than 150nm, and more than 85% of the particles are inside the tungsten grains. The particles are composed of a WO3 shell layer on the surface and a HfO2 core layer inside. The strain rate in the uniaxial tensile test is a constant 2×10 -4 s -1 The performance test results show that the tensile strength of nano-phase change particle dispersion strengthened tungsten alloy at room temperature is as high as 1.53GPa, and the elongation is >7.5%, indicating that the material has excellent plasticity at room temperature. Figure 4 As shown, the tungsten alloy prepared at 800°C has a certain strain hardening ability, and the tensile strength is maintained at 1.13 GPa.
[0052] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A nano phase change particle dispersion strengthened tungsten alloy, characterized in that: The tungsten alloy is composed of a W matrix and HfO2@WO3 nanoparticles with a core-shell structure, wherein the particle size of the HfO2@WO3 nanoparticles is 5-150 nm. In terms of weight percentage, the content of the HfO2@WO3 nanoparticles with a core-shell structure is 0.2-2.0%, and the content of the W matrix is 98.0-99.8%.
2. The nano phase change particle dispersion strengthened tungsten alloy according to claim 1, characterized in that: In terms of weight percentage, the content of the HfO2@WO3 nanoparticles is 0.2-1.0%, the content of the W matrix is 99.0-99.8%, and the particle size of the HfO2@WO3 nanoparticles is 5-80 nm.
3. The nano phase change particle dispersion strengthened tungsten alloy according to claim 1, characterized in that: In terms of weight percentage, the content of the HfO2@WO3 nanoparticles is 1.0-2.0%, the content of the W matrix is 98.0-99.0%, and the particle size of the HfO2@WO3 nanoparticles is 5-120 nm.
4. The nano phase change particle dispersion strengthened tungsten alloy according to claim 1, characterized in that: The tungsten alloy is obtained by introducing nano HfH2 particles into a W matrix under a heated, pressurized and oxygen-free environment and performing thermomechanical deformation processing to in-situ generate HfO2@WO3 particles with a core-shell structure on the W matrix by utilizing phase changes during the heating and cooling process.
5. A method for preparing the nano phase change particle dispersion strengthened tungsten alloy as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Using tungsten powder and nano-scale HfH2 powder as raw materials, mixing them evenly in an oxygen-free environment to obtain alloy powder; (2) sintering the alloy powder under heating and pressure conditions to obtain a tungsten alloy block; (3) Performing thermomechanical deformation processing on the tungsten alloy block to obtain the nano phase change particle dispersion strengthened tungsten alloy.
6. The preparation method according to claim 5, characterized in that: The particle size of the tungsten powder is 0.2-6 μm, and the oxygen content is 800-2500 ppm. The particle size of the nano-scale HfH2 powder is 20-50 nm, and the oxygen content is ≤0.5 wt%.
7. The preparation method according to claim 5, characterized in that: The oxygen-free environment is one of argon, nitrogen or vacuum environment, the temperature of heating and pressurizing is 1600-1800° C., the pressure is 30-60 MPa, and the sintering time is 0.2-4 h.
8. The preparation method according to claim 5, characterized in that: The temperature of the thermomechanical deformation processing is 1000-1500°C.
9. The preparation method according to claim 5, characterized in that: The thermomechanical deformation processing is one or a combination of two or more of high-energy forging, rolling, rotary forging and extrusion.
10. The preparation method according to claim 9, characterized in that: The number of passes of the thermomechanical deformation processing is 4-10, the deformation amount of each pass is 5-20%, and the total deformation amount is greater than or equal to 60%.